2022
DOI: 10.1002/hep.32324
|View full text |Cite
|
Sign up to set email alerts
|

Compromised hepatic mitochondrial fatty acid oxidation and reduced markers of mitochondrial turnover in human NAFLD

Abstract: Background and Aims NAFLD and its more‐advanced form, steatohepatitis (NASH), is associated with obesity and is an independent risk factor for cardiovascular, liver‐related, and all‐cause mortality. Available human data examining hepatic mitochondrial fatty acid oxidation (FAO) and hepatic mitochondrial turnover in NAFLD and NASH are scant. Approach and Results To investigate this relationship, liver biopsies were obtained from patients with obesity undergoing bariatric surgery and data clustered into four gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 61 publications
12
98
2
1
Order By: Relevance
“…The results of this study showed that hepatic mitochondrial complete FAO was reduced by ~40-50% in subjects with NASH compared to the control subjects with normal histology. This decrease corresponded with increased hepatic mitochondrial reactive oxygen species production and reductions in the markers of mitochondrial biogenesis and mitophagy [131]. These findings support a link between mitochondrial dysfunction and NAFLD/NASH in humans and suggest that impaired hepatic fatty acid oxidation and reduced mitochondrial quality are strongly linked to increasing NAFLD severity in patients with obesity.…”
Section: Fao and Nafldsupporting
confidence: 62%
See 1 more Smart Citation
“…The results of this study showed that hepatic mitochondrial complete FAO was reduced by ~40-50% in subjects with NASH compared to the control subjects with normal histology. This decrease corresponded with increased hepatic mitochondrial reactive oxygen species production and reductions in the markers of mitochondrial biogenesis and mitophagy [131]. These findings support a link between mitochondrial dysfunction and NAFLD/NASH in humans and suggest that impaired hepatic fatty acid oxidation and reduced mitochondrial quality are strongly linked to increasing NAFLD severity in patients with obesity.…”
Section: Fao and Nafldsupporting
confidence: 62%
“…More recently, our group has investigated the relationship between NAFLD/NASH, mitochondrial fatty acid oxidation in liver, and hepatic mitochondrial quality in human subjects [131]. We obtained liver biopsies from patients with obesity undergoing bariatric surgery and correlated the liver histology to the mitochondrial fatty acid oxidation measured in the liver tissue.…”
Section: Fao and Nafldmentioning
confidence: 99%
“…Deficient ETC functioning would render hepatocytes more susceptible to oxidative damage upon FFA excessive arrival, thus sustaining a vicious circle between hampered FA oxidative capacity and increased ROS production [ 123 , 227 ]. In line with the results of preclinical investigations, studies indicate that mitochondrial redox balance, appropriate FA oxidation and ETC capacity are important components defense mechanisms against NAFLD in humans [ 228 , 229 ].…”
Section: Oxidative Stress In Nafldmentioning
confidence: 84%
“…In addition, mitophagy plays a role activating of the inflammasome [ 106 ]. Moore et al have recently linked compromised mitochondria to increasing NAFLD severity in patients with obesity [ 141 ]. They reported a 40–50% reduction in β-oxidation in NASH patients, associated with increased hepatic ROS production and a reduction in markers of mitochondrial biogenesis, autophagy, mitophagy, fission, and fusion [ 141 ].…”
Section: Pathogenesis Of Nafldmentioning
confidence: 99%